2016
DOI: 10.1515/libri-2016-0035
|View full text |Cite
|
Sign up to set email alerts
|

The Contribution of Effective Library and Information Services to Academic Achievements at Some Selected Universities in Ghana

Abstract: This paper, which is largely based on the findings of my doctoral study, investigated the contribution of effective library and information services to academic achievements at universities in Ghana. The main objective of this study was to assess and explore the effectiveness of library and information services and establish its contribution to efficient academic work. The researchers adopted a mixed methods approach in which both qualitative and quantitative research approaches are used in a single study. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 4 publications
2
8
0
Order By: Relevance
“…While they are undoubtedly interested in library collections (especially online information resources), the services like the librarians' expertise need marketing actions -the researcher are often unaware of this kind of possible support (Nel & Fourie, 2016). It is obvious that the situation may be different in a developing country like Ghana, thus in the opinion of faculty and students traditional services like Internet services, provision of study space and literature searches were services that contributed most to academic achievements (Cobblah & van der Walt, 2016). Ko, Shim, and Pyo (2016) considered the willingness of Korean scholars and students to pay for library services with a not very surprising conclusion that neither respondents from private nor public universities were interested in such a solution.…”
Section: Research Support: Librarians' and Scholars' Approach To Collmentioning
confidence: 99%
See 1 more Smart Citation
“…While they are undoubtedly interested in library collections (especially online information resources), the services like the librarians' expertise need marketing actions -the researcher are often unaware of this kind of possible support (Nel & Fourie, 2016). It is obvious that the situation may be different in a developing country like Ghana, thus in the opinion of faculty and students traditional services like Internet services, provision of study space and literature searches were services that contributed most to academic achievements (Cobblah & van der Walt, 2016). Ko, Shim, and Pyo (2016) considered the willingness of Korean scholars and students to pay for library services with a not very surprising conclusion that neither respondents from private nor public universities were interested in such a solution.…”
Section: Research Support: Librarians' and Scholars' Approach To Collmentioning
confidence: 99%
“…A cademic libraries are institutions whose mission consists of supporting the academic community, among others, scholars both in research and teaching activities. According to Cobblah and van der Walt (2016) "the library is the physical manifestation of the core values and activities of academic life and the library's central role in the academic community is unquestionable." However, is that really true?…”
mentioning
confidence: 99%
“…In a study of seven universities in the USA and Australia in 2004 to 2006, it was discovered that half of the scholarly article readings were for research purpose. Furthermore, Cobblah and Van Der Walt (2016), Dunne et al (2013) and Botha et al (2009) demonstrated explicit value of libraries by assessing user satisfaction of library services, resources and expertise. A survey conducted by the School of Library and Information Science at the University of South Carolina reported that 92% of users think that library improves the overall quality of life and 73% feels that the library enhances personal fulfilment (Jaeger et al, 2011).…”
Section: Demonstrating the Value Of Academic Librarymentioning
confidence: 99%
“…Furthermore, printing and photocopying facilities were found to have significant impact on user satisfaction in the Sur University College Library, Sultanate of Oman (Sriram and Rajev, 2014). Also, Cobblah and Van Der Walt (2016) investigated the contribution of effective library and information services to academic achievements at universities in Ghana and concluded that there was a correlation between effective library and information services, and academic achievements at the universities in Ghana. The study also established that library users were generally satisfied with the services provided.…”
Section: User Satisfaction As An Indicator Of Library Valuementioning
confidence: 99%
“…Researchers from Australia described a way to expand a library's offer through providing the students with technical support in their use of information and communication technologies (Renner et al, 2014). Cobblah and van der Walt (2016) established that Internet services were the library services that contributed most to academic achievements of students at the universities in Ghana. In China a study was carried out among students and scientists regarding their need for support from the librarians in relation to management and storage of data gathered during the process of conducting research (Liu & Ding, 2016).…”
Section: Digital Technologies And…mentioning
confidence: 99%